Islamic Shangri-La Inter-Asian Relations and Lhasa's Muslim Communities, 1600 to 1960 - Atwill, David (University of California Press, 2018)
"Islamic Shangri-La transports readers into the heart of the Himalayas by tracing the rise of the Tibetan Muslim (Khache) community from the early 17th century to the present. Over the past four centuries, the Tibetan Muslims advised several Dalai Lamas, contributed to Tibetan music and literature, and engaged in transregional trade with many of Tibet's neighbors. Deftly blending contemporary media accounts and interviews with archival documents, this book brings the frustrations and hopes of Tibetan Muslims, and thus of Tibet, to life. Less a history of religion than a history of the Himalayas, the book explores the eddying currents of peoples and states generally excluded from traditional histories of Asia. Its focus on the Tibetan Muslims' multifaceted role in Tibetan society highlights Tibet's broader inter-Asian positioning and delves into the intertwined relationship between Tibet and Nepal, Kashmir, and other Himalayan states. The story of the Tibetan Muslims provides a new perspective on a history we thought we knew quite well. Illuminating their positioning within the dynamics of Asian state formation with a particular emphasis on the dramatic events of early to mid-20th century, the book opens an unparalleled examination of the long shadows of Tibet's past on today's Asia."